TATA KELOLA TERINTEGRASI DALAM MEMINIMALISIR TINDAK PIDANA KORUPSI PADA IMPOR TANGKI OKSIGEN DI PERBATASAN ENTIKONG - Alunaza, Hardi; Putri, Anggi; Ernianda, Annisa; Nur Shafitri, Desy (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Being geographically close to Malaysia made them into good political relations; the example was the Import of Oxygen Tanks during pandemic in 2020-2021. Trading is carried out specifically after the Import Agreement which was requested directly by the Governor of West Kalimantan. The Oxygen Import Agreement requires an integrated action between the institutions in order to minimize corruption. The research is elaborated through three main discussions, based on the Border Governing Theory and Sovereignty Concept on a qualitative approach and descriptive method. First, the Legal Basic for Border Management. Second, the Export-Import Process and Sectoral Cooperation through the Oxygen Tank import process. Third, the success of Integration Governance process to reduce the Corruption. The purpose of this study is to see the success in relation to minimizing corruption in the Export of Oxygen Tanks at the Entikong Border.